Analisis Pengaruh Pertumbuhan Penduduk dan Tingkat Pengangguran Terhadap Kemiskinan di Provinsi Lampung Tahun 2014-2023 - Putri, Nayyara Rafa; Sudirman, Ginda Nugraha; Desmawan, Deris (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
Many countries are dealing with poverty, and Indonesia is no exception. The inability to meet the most basic needs is cruel when we talk about poverty. this research aims to analyze the relationship between poverty in Lampung Province and economic development, unemployment, and its contribution. For this study, we used secondary data collected by the Central Bureau of Statistics for 2019-2023. Multiple linear regression analysis is used as a Data Testing Tool. Based on the research output, the poverty rate in Lampung Province is influenced by economic growth and unemployment. The authors of the study argue that government should be able to encourage business expansion and the creation of a business activity workforce.